The ISPRA Mediterranean Coastal Wave Forecasting system: evaluation and perspectives. (12th February 2016) - Inghilesi, R.; Orasi, A.; Catini, F.
Abstract : The Mediterranean Coastal Wave Forecasting (MCWAF) system has been operational at the Italian National Institute for Environmental Protection and Research (ISPRA) since September 2012. The principal aim of the system is to provide medium-range wind-generated wave forecasts for the Mediterranean on a regional and coastal scale. The detailed information about the sea state near the shore also allows the use of the results to be applied to coastal investigations related to the wave climate – for example, making estimates of wave power and identifying biological habitats.